2007
DOI: 10.1016/j.eurpsy.2007.01.741
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorder in patients with multiple sclerosis

Abstract: Thirty percent of our subjects were diagnosed as PPD. Patients with PPD had more severe depressive symptoms during the last 3 months of pregnancy, higher rates of history of depression, PPD, postpartum blues, premenstrual dysphoric disorder, parental depression, poor social support, stressful life events during last 1 year, and problems in marriage as compared those without PPD. There was no significant difference between groups with respect to type of birth and pregnancy, history of abortion and curettage, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some authors [60,61] were unable to find significant correlations between the EDSS score and depressive scores. Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 93%
“…Some authors [60,61] were unable to find significant correlations between the EDSS score and depressive scores. Most studies, however, found that MS patients with higher EDSS scores had significantly higher depression scores, while significant positive correlations were found between the EDSS and depression scores [62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 93%
“…[27][28][29] In cases of advanced MS, the most common psychological disorder reported is a reactive depression. 30 Chwastiak et al 31 also found that particularly those in the advanced stages of MS suffer more from depressive symptoms. Depression is thought to occur because of physical impairment, dependency on others as well as an uncertainty about their finances, job, and future.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment methods or psychological states of these systemic or chronic diseases can cause sexual dysfunction indirectly. In a study that contained 17 MS cases, psychiatric disorders were found in 12.56% [27] and in another study psychiatric disorders were found in 38% of patients with eosinophilic fasciitis [28]. Even though it is known that chronic diseases can cause psychiatric disorders by causing mood disorders, the number of studies that examine relations of these diseases with ED are limited.…”
Section: Discussionmentioning
confidence: 99%